The ferroform and glycoform landscape of human milk lactoferrin dissected through hybrid mass spectrometric approaches - Zhu, Jing; Bauzá-Martinez, Julia; Gouw, Joost W.; Zhao, Xianfeng; Heck, Albert J. R.; Stahl, Bernd; Reiding, Karli R.; Dingess, Kelly A. (Frontiers in Nutrition, 2025)
Human milk lactoferrin (hmLF), a sialic acid-rich iron-binding milk glycoprotein, is essential for infant development, playing a key role in immune defense and gut maturation. Despite its importance, the diversity of hmLF proteoforms, including the relationship between glycosylation profiles (glycoforms) and iron-binding states (ferroforms), has not been systematically characterized. To address this, we used a hybrid mass spectrometry (MS) approach, combining bottom-up glycoproteomics and ion-exchange (IEX) native MS, to analyze hmLF from three human milk donors across lactation. Bottom-up glycoproteomic results revealed that Asn642 remained predominantly not glycosylated, while Asn156 and Asn497 were frequently occupied with biantennary glycans exhibiting variable fucosylation and sialylation. Notably, glycan heterogeneity displayed a site-specific pattern, decreasing consistently in both donors over lactation. Additionally, we used an IEX-native MS strategy to obtain a full picture of the glyco- and ferroforms coexisting in human milk at late lactation stages. IEX separated LF molecules primarily by iron content rather than glycan composition, resulting in five LF fractions with varying iron-loading and glycosylation levels. Native MS full proteoform profiling of these fractions validated that most LF molecules were glycosylated at two of the three available sites, likely Asn156 and Asn497, yet revealed a minor pool of proteoforms glycosylated at all three sites. Careful evaluation of individual fractions and compiled data revealed no clear correlation between ferroform and N-glycosylation profiles. These findings provide a detailed overview of hmLF molecular heterogeneity, offering valuable insights for advancing nutritional product development and understanding this bioactive protein’s functional role.